Analysis of School Financial Management in TK Negeri Pembina 2 Bantan Kabupaten Bengkalis - Nurul Qhoimah; Erni Munastiwi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
In financial management educational institutions, it is very important to know what the school needs. With clear and appropriate finances, it will affect the school's operations and education at the school. The purpose of this article is to find out how to manage finances in TK Negeri Pembina 2 Bantan. Collecting data through observation, interviews and documentation. The results of the analysis show that financial management at TK Negeri Pembina 2 Bantan is carried out by planning for the management of BOS funds in 2021-2022 starting with the preparation of the RKAS and the preparation of the RAB as well as the implementation of the use and finally bookkeeping. The realization of BOS fund management has complied with the principles referred to in Government Regulation no. 48 of 2008 article 59.